Monitoring Vegetation Growth of Spectrally Landsat Satellite ImageryETM+ 7 & TM 5 for Western Region of Iraq by Using Remote SensingTechniques. - Mashee, Fouad; Zaeen, Ahmed; Hadi, Gheidaa (Iraqi Journal of Science, 2024)
Landsat-5 Thematic Mapper (TM) has been imaging the Earth since March 1984and Landsat-7 Enhanced Thematic Mapper Plus (ETM+) was added to the series ofLandsat instruments in April 1999. In this paper the two sensors are used tomonitoring the agriculture condition and detection the changing in the area of plantcovers, the stability and calibration of the ETM+ has been monitored extensivelysince launch although it is not monitored for many years, TM now has a similarsystem in place to monitor stability and calibration. By referring to statistical valuesfor the classification process, the results indicated that the state of vegetation in 1990was in the proportion of 42.8%, while this percentage rose to 52.5% for the samestudy area in 2002.